Age, sex, and region adjusted concentrations of chromium and nickel in lung tissue. - Kollmeier, H (1990)
Chromium (Cr) and nickel (Ni) concentrations were measured in lung tissue from 110 random necropsies by means of atomic absorption spectrometry. The subjects originated from the Ruhr district (Bochum (71 cases) and Dortmund (16 cases) areas), which has been defined as a particular pollution area with locally high Cr and Ni emissions, and from Münster and vicinity (23 cases). The Cr and Ni concentrations in lung tissue of the subjects from the Ruhr district (3.09 (SD 2.99) micrograms Cr/g, 0.65 (SD 0.94) micrograms Ni/g dry weight of lung) were 4.8 and 2.8 times higher than those from Münster (0.66 (SD 0.49) micrograms Cr/g, 0.17 (SD 0.11) micrograms Ni/g dry weight of lung). Concentrations of Cr and Ni in men were twice those in women. All data showed an age dependent increase of Cr and Ni in the lung (about 2.4% a year for Cr and 3% a year for Ni) and Cr and Ni values showed a high correlation (r greater than or equal to 0.9). Thus it was possible to calculate age, sex, and region adjusted expected values of pulmonary Cr and Ni concentrations, and to identify the difference between expected and observed values. This might be helpful to interpret measurements in individual cases and in epidemiological studies. With this procedure the six cases of bronchial carcinoma in the series were shown to have pulmonary Cr and Ni concentrations that were mostly well above the predicted values, and it was possible to give a rough estimate of the degree of deviation.